Correlative analysis of blood pressure and other biochemical parameters with type 2 DM subjects - Ferdous, Jannatul; Laila, Runa; Ahmed, Shamim; Begum, Nasreen; Begum, Ismat Ara; Sen, Moushumi; Yousuf, Abul Kalam Mohammad; Ferdousi, Sohani (Northern International Medical College Journal, 2015)
Objective : To determine the association of blood pressure and other biochemical parameters with type 2 DM subjects. Methodology : This was an observational study with case control design was conducted in the Biomedical Research Group, Research Division, Bangladesh Institute of Research and Rehabilitation in Diabetes ,Endocrine Metabolic Disorders (BIRDEM), Dhaka Bangladesh, during the period of July 2008 to June 2009. A total of 153 subjects were included in study of which 63 belonged to T2 Diabetes Mellitus group and 90 were healthy Controls. Insulin glucose ratio were assayed in patients and controls and identified the association, using standardized assay methods. We also assessed the type 2 diabetic patients who had significantly raised Fasting blood sugar, insulin HOMA-B %= B cell function assessed by homeostasis model assessment to compared with the healthy controls. Correlation analysis of HOMA-B % with biochemical parameters, blood pressure, fasting and post prandial glucose also analysed. Results : Age of Control and type 2 DM subjects ( Mean±SD),P-value] were (46 ± 8.31) and (47 ±7.58), (P=0.326) respectively and BMI, among subject and control (kg/m2), (Mean ± SD), (24 ± 3.96, 25 ± 2.72 p=0.754). WHR [cm, (Mean±SD), p=<0.001], showed significant difference between T2 DM and healthy subjects. The median (range) of the glucose and insulin ratio of the study group, there was significant difference between Control vs. T2DM (p<0.001). Systolic blood pressure[S-BP, mean±SD] & Diastolic blood pressure [D-BP, mean±SD] were significant in T2DM as compared to control subjects ( p= 0.008) ( p= 0.003) respectively ; Fasting plasma glucose levels [mmol/l, (Mean± SD)] , post prandial plasma glucose level [mmol/l, (Mean± SD)]and the HOMA%B level median (range) among subject and control of the study group[(8.27±2.19) , (11.79 ± 2.69), 71 ( 4.90 - 391.30)] were a significant difference in between Control vs type2 DM (p <0.001), (p <0.001)and. (p <0.001) respectively. Conclusion : In this study, boty systolic and diastolic blood pressure, blood glucose level and insulin status and WHR were found the significant parameters for maintaining type to DM under control condition. Development of hypertension cardio vascular disease and other complication can be prevented on keeping these parameters in normal level. Northern International Medical College Journal Vol.5(1) 2013: 306-308